Chronic p38 mitogen-activated protein kinase inhibition improves vascular function and remodeling in angiotensin II-dependent hypertension. (July 2016) - Potthoff, SA; Stamer, S; Grave, K; Königshausen, E; Sivritas, SH; Thieme, M; Mori, Y; Woznowski, M; Rump, LC; Stegbauer, J
Introduction: An excess of angiotensin II (Ang II) causes hypertension and vascular injury. Activation of mitogen-activated protein kinase p38 (p38-MAPK) plays a substantial role in Ang II-dependent organ damage. Recently, we showed that p38-MAPK activation regulates the pressor response to Ang II. This study evaluates the effect of chronic p38-MAPK inhibition in Ang II-dependent hypertension. Materials and methods: C57Bl/6J mice were infused with Ang II for 14 days and either treated with the p38-MAPK inhibitor BIRB796 (50 mg/kg/day) or the vehicle as the control. We assessed vascular function in the aorta and isolated perfused kidneys. Results: Chronic p38-MAPK inhibition did not alter blood pressure at the baseline, but attenuated Ang II-induced hypertension significantly (baseline: 122 ± 2 versus 119 ± 4 mmHg; Ang II: 173 ± 3 versus 155 ± 3 mmHg; p < 0.001). In addition, BIRB796 treatment improved vascular remodeling by reducing the aortic media-to-lumen ratio and decreasing the expression of the membrane metalloproteinases (MMP) MMP-1 and MMP-9. Moreover, renal vascular dysfunction induced by chronic Ang II infusion was significantly ameliorated in the BIRP796-treated mice. Acute p38-MAPK inhibition also improved vascular function in the aorta and kidneys of Ang II-treated mice, highlighting the important role of p38-MAPK activation in the pathogenesis of vascular dysfunction. Conclusions: Our findings indicated there is an important role for p38-MAPK in regulating blood pressure and vascular injury, and highlighted its potential as a pharmaceutical target.